Knowledge, Attitude and Practice of Weight Reduction Among Overweight and Obese Adolescent Students: Life Sciences-Pharmacology - Sanjay Bhujbal, Akshata; Baby, Biji; T., Poovishnu Devi (International Journal of Life Science and Pharma Research, 2022)
Overweight/obesity is usually associated with some complications that adversely affect the health of the individuals. Due to an increase in sedentary life style, increased consumption of junk food and lack of physical exertion, there's an impact on their body image by increase in weight leading to overweight and obesity. This study assessed the level of knowledge, attitude and practice of weight reduction among overweight and obese adolescent students in Karad community. This cross-sectional study included 94 overweight and obese individuals in which, 55 were females and 39 were males. A self-administered questionnaire was used to collect data on sociodemographic characteristics, knowledge, attitude and practice of weight reduction among overweight and obese adolescent students. A total of 94 participants were included in this study, among which 57% participants had good knowledge on weight reduction, the attitude regarding weight reduction in our study was observed that 52% of participants had a positive attitude. The level of practice was less compared to knowledge and attitude, 19% participants actually participated in weight reduction programs. The level of good knowledge and positive attitude is not enough to prevent complications of overweight and obesity. More efforts should be taken to increase the practice of overweight and obese adolescent students by active participation in weight reduction program. The study is important to highlight the importance of weight reduction programs in overweight and obese adolescent students. It also indicates the severity of ill effects of overweight and obesity. As many adolescents are facing the problems of overweight and obesity, it is important to make awareness of weight reduction programs. The result of this study indicates that there is a need to implicate the weight reduction programs in overweight and obese adolescent students.